2021
DOI: 10.1177/0363546521995184
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Effects of Bupivacaine on the Viability and Mechanics of Native and Engineered Cartilage Grafts

Abstract: Background: Although the toxic effects of bupivacaine on chondrocyte monolayer culture have been well described, its cellular and mechanical effects on native and engineered articular cartilage remain unclear. For the repair of articular cartilage defects, fresh autologous and allogenic cartilage grafts are commonly used, and engineered cell-based therapies are emerging. The outcome of grafting therapies aimed at repairing damaged cartilage relies largely on maintaining proper viability and mechanical suitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
(75 reference statements)
0
13
1
Order By: Relevance
“…Several studies have historically shown that bupivacaine and other local anesthetics are chondrotoxic, both with increasing dosage and time of exposure. 2,4,19 Although there Figure 3. Mass spectrometry results for collagen content (using OHP as a proxy) and collagen crosslinking (using pyridinoline as a proxy).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have historically shown that bupivacaine and other local anesthetics are chondrotoxic, both with increasing dosage and time of exposure. 2,4,19 Although there Figure 3. Mass spectrometry results for collagen content (using OHP as a proxy) and collagen crosslinking (using pyridinoline as a proxy).…”
Section: Discussionmentioning
confidence: 99%
“…26 The short-term study performed by Oyadomari and colleagues found no effect of bupivacaine exposure on compressive mechanical properties 24 hours after exposure. 2 It was hypothesized that a longer incubation period could allow damage from bupivacaine exposure to extend to the compressive properties of explants. However, that was not seen in this study and suggests that either such effects may occur earlier than 3 weeks and be transient, these hypothetical decreases need longer than 3 weeks to appear, or single bupivacaine exposure may not affect the compressive properties at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The collagen and GAG content were normalized to WW and DW. 4,18 Creep Indentation Testing A creep indentation apparatus machine was used to assess the viscoelastic compressive properties of explants that had been frozen for 2 weeks in protease inhibitor. 1 ImageJ was used to measure the thickness of the specimens by graphically scaling the thickness of the sample to a ruler underneath the sample.…”
Section: Quantitative Biochemistrymentioning
confidence: 99%